The Election Campaign of 10-N in Spain and its reflex in Latin American Press - Gómez-Calderón, Bernardo (2021)
The paper analyzes the informative coverage of 9 Latin American newspapers on the general election held in Spain on November 10, 2019. This is considered an important event that helped close a turbulent period of the national political life. A content analysis sheet was applied to all texts regarding the campaign appeared between November 1 and 11 (n = 35), considering, among other variables, location, extension, authorship, sources, genres, nature of the content and frame. The results allow concluding that the selected newspapers dedicated a wide space to the November 10 election. Furthermore, media outlet granted part of their coverage an interpretive dimension and offered a vision on the campaign dominated by the strategic and game frames, since they placed the focus on the polls and the possibility of post-electoral agreements.